The Role of Al-Mumtaz Application in Increasing Student’ Arabic Learning Motivation in State Madrasah Tsanawiyah of Padang Panjang City - Rahmat Hidayat; Nur Hasaniyah; Abdul Muntaqim Al Anshory (Journal of Social Science Utilizing Technology, 2024)
Background. Learning motivation is an important factor in educational success, including in learning Arabic at Madrasah Tsanawiyah Negeri Kota Padang Panjang. The Al-Mumtaz app has been designed to support the learning process by offering interactive and engaging methods. However, the effectiveness of this application in increasing student learning motivation has not been studied much. Purpose. This study aims to examine the role of the Al-Mumtaz application in increasing students' motivation to learn Arabic at Madrasah Tsanawiyah Negeri Kota Padang Panjang. The main focus of this study was to find out the extent to which such applications can affect student learning motivation. Method. This research uses quantitative methods with experimental design. The research sample consisted of 60 students of Madrasah Tsanawiyah Negeri Kota Padang Panjang who were divided into two groups: an experimental group using the Al-Mumtaz application and a control group using conventional learning methods. Data were collected through learning motivation questionnaires before and after the intervention, as well as in-depth interviews to support quantitative data. Results. The results showed that there was a significant increase in student motivation in the experimental group compared to the control group. Students who use the Al-Mumtaz app show higher levels of motivation in terms of interest, activeness, and commitment to Arabic language learning. Conclusion. Al-Mumtaz application significantly increases students' motivation to learn Arabic at Madrasah Tsanawiyah Negeri Kota Padang Panjang